Pengaruh Digital Marketing dan Kualitas Produk Terhadap Keputusan Pembelian Mie Instan Lemonilo di Jakarta - Nandha Puspita; Rani Rani; Purwatiningsih Purwatiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Instant noodle Lemonilo are a newcomer to Indonesia. To be able to compete with other instant noodle brands, Lemonilo is doing digital marketing on a large scale to attract consumers. Starting from doing advertisements on television, to social media. In addition, Lemonilo carries the theme of healthy instant noodles which are safe for consumption by all people and uses quality ingredients (no MSG, food coloring and preservatives). Based on these observations, the authors conducted this research. Data was collected using a questionnaire given to on instant noodle Lemonilo customers. The sample used in this study was 50 respondents using a systematic random sample method. The analytical tool used is descriptive (primary data) by using a questionnaire assisted by a Likert scale and given to respondents. The analytical tool used is SPSS software version 25. The results of this study prove that: 1) Digital Marketing has a partial positive and significant effect on Purchase Decisions with a Digital Marketing. 2) Product quality has a positive and significant partial effect on purchasing decisions. 3) Digital Marketing and Product Quality have a positive and significant simultaneous effect on Purchase Decisions.